PERFORMANCE OF SPENT COFFEE GROUNDS ACTIVATED CARBON AND RIVER SAND AS FILTRATION MEDIA FOR TOTAL SUSPENDED SOLIDS REMOVAL IN ABATTOIR WASTEWATER TREATMENT - Rahman, Arief; Nisah, Khairun; Naufal Fawwaz, Atha (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2026)
Abattoir wastewater contains high levels of total suspended solids (TSS) and might cause negative impacts on the environment if discharged directly without being treated in advance. Filtration methods can be used to treat abattoir wastewater, especially in TSS removal, utilizing filtration media such as sands. and activated carbon. The objective of this research is to discover the potential of spent coffee grounds (SCG) activated carbon and river sand as filtration media for TSS removal in abattoir wastewater treatment. The research was conducted by using dual media filtration, consisting of SCG activated carbon and river sand, 15 cm and 30 cm in thickness, respectively. The result shows that the combination of SCG activated carbon and river sand can reduce the TSS levels of abattoir wastewater from 164 mg/L to 37 mg/L, with 77.43% removal percentage and met the quality standard, which is 100 mg/L. Based on the result, it is concluded that the combination of SCG activated carbon and river sand has good potential as filtration media for TSS removal in abattoir wastewater treatment, and further improvements can be conducted to enhance the efficacy.